Africa Development Indicators 2007 - World Bank (Washington, DC, 2013)
The Africa Development Indicators 2007 essay explores the patterns of growth in Sub- Saharan Africa over the past three decades. It finds that the volatility of growth-an outcome of conflict, governance, and world commodity prices-has been greater than in any other region. Volatility has dampened expectations and investments-and has obscured some periods of good performance for some countries. The essay shows that pickups in growth were seldom sustained- indeed, that they were often followed by ferocious declines, and hence, Africa's flat economic performance over 1975-2005. The essay shows that avoiding economic declines is as important as promoting growth. Indeed, it may be more important for the poor, who gain less during the growth pickups and suffer more during the declines. The essay discusses a key question for economic policymakers in Africa: how best to sustain pickups in growth and its benefits. The Africa Development Indicators suite of products is designed to provide all those interested in Africa with a set of indicators to monitor development outcomes in the region and is an important reference tool for those who want a better understanding of the economic and social developments occurring in Africa.